56th AIAA/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2015
DOI: 10.2514/6.2015-2066
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and Experimental Studies on Delamination Arrest Features in Aircraft Composite Structures

Abstract: Delamination is the critical damage type for integrated carbon fiber structures, which are employed in primary aircraft structures. In order to minimize the danger, one common solution is to install fasteners, clamping the laminate together and partially arresting the delamination. Current research has indicated that multiple fasteners installed in series do not fully arrest delaminations, instead merely slowing and redirecting the propagation of the crack, first by compressing the lamina together and second b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…As a result, effort has been put into predicting the fatigue delamination response of composites under various loading conditions. Much of the foundational work revealed that the matrix properties dominated the delamination fatigue response [28] while more recent work found that the introduction of fasteners to the system will alter the response [29] [30].…”
Section: Fatigue In Compositesmentioning
confidence: 99%
“…As a result, effort has been put into predicting the fatigue delamination response of composites under various loading conditions. Much of the foundational work revealed that the matrix properties dominated the delamination fatigue response [28] while more recent work found that the introduction of fasteners to the system will alter the response [29] [30].…”
Section: Fatigue In Compositesmentioning
confidence: 99%